Prevalence And Predictors of Exposure to Second-Hand Smoke Among Never-Tobacco Smokers - Sharma, Deepak; Goel, Naveen Krishan (National Journal of Community Medicine, 2022)
Background: Exposure to Second-hand tobacco smoke (SHS) harms health. It is a risk factor for various diseases like asthma, hypertension, diabetes, heart disease and lung cancer. This study aimed to determine the prevalence and predictors of second-hand tobacco smoke among adult never-smokers. Methods: A cross-sectional study was conducted among 220 participants aged 18 years and above. A pre-tested questionnaire was used to elicit information regarding exposure to second-hand smoke at the home, workplace and various public places. The data was analysed using the Epi Info software for windows. Results: The second-hand smoke exposure at home and workplace was 11.4% and 19.1%, respectively. The SHS exposure at bus stops, public transport, government buildings and health care facilities were 33.3%, 13.0%, 7.6% and 3%, respectively. The in-home study participants with a current tobacco smoker, family member and/or friend had comparatively higher exposure to second-hand tobacco smoke. In the workplace and or public places, male study participants and illiterate individuals had higher exposure to second-hand tobacco smoke. Conclusion: The observed level of SHS exposure among non-smokers is a public health concern. Family members should not allow anyone to smoke in their home environment. The public health law prohibiting tobacco smoking in workplaces and public places needs further strengthening.